Edge turbulence transport during ELM suppression with n = 4 resonant magnetic perturbation on EAST. (6th March 2023) - Liu, S.C.; Liang, Y.; Li, L.T.; Tang, T.F.; Wu, X.H.; Yan, N.; Shi, T.H.; Li, G.S.; Ye, K.X.; Meng, L.Y.; Ding, R.; Sun, Y.; et al.
Abstract: The edge turbulence characteristics and the induced radial transport have been investigated in edge localized mode (ELM) suppression by using the n = 4 resonant magnetic perturbation coils on EAST, with q 95 = 3.6 and the electron collisionality ν e ∗ ≈ 0.5. During ELM suppression, the edge turbulence is enhanced dramatically, as measured by the reciprocating probe and the poloidal correlation reflectometry. In the near SOL, the low frequency turbulence (<30 kHz) has a large fluctuation level and propagates along the ion diamagnetic drift direction with a speed of 0.35 km s −1 in the plasma frame; an n = 1 electromagnetic mode around 120 kHz with a small k θ (∼0.15 cm −1 ) appears when the ELM is suppressed; weak broadband turbulence between 40–120 kHz propagates in the electron diamagnetic drift direction with a velocity of 3.4 km s −1 in the plasma frame. During the ELM suppression, the radial turbulent particle flux, calculated in both the time and frequency domains, is much higher (can be up to five times) than that in the inter-ELM phase. Furthermore, the low frequency turbulence (<30 kHz) dominates the cross-field particle transport. The 120 kHz electromagnetic mode also contributes to outward particle flux, which is relatively small. A set of CGYRO simulations are performed to illustrate the nature of the 120 kHz electromagnetic mode and the low frequency turbulence, suggesting that the former is the micro-tearing mode and the latter is the ion temperature gradient mode. The bispectral analysis suggests a strong three-wave coupling between the low frequency and high frequency turbulence (>250 kHz), which could be beneficial to form the observed turbulent transport. The estimated upstream cross-field particle flux is consistent with the total particle flux deposited on divertor targets, demonstrating that the enhanced radial turbulent particle transport is an important mechanism for particle exhaust in ELM suppression.